PERBEDAAN PERAWATAN TALI PUSAT TERTUTUP DAN TERBUKA TERHADAP LAMA PELEPASAN TALI PUSAT DI PUSKESMAS SRONDOL DAN PUSKESMAS NGESREP KOTA SEMARANG - Wiwid Ria Trijayanti; Listyaning Eko Martanti; Sri Wahyuni (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2020)
The umbilical cord infection characterize by red, swollen, suppurate,and smelling. This infection can occur treatment that does not hygiene requirements. The treatment uses a frequently replaced sterile gauze pad. Another way to allow an open umbilical cord with clean water and then dried.The goals, know the difference of closed and open umbilical cord care to the umbilical discharge at Srondol Public Health Center and Ngesrep Semarang City. This research is a kind of experiment with posttest only control group design. Population of newborn at Puskesmas Srondol and Ngesrep by purposive sampling technique. Sample 20 was given a closed care and 20 were given an open care. Treatment is measured from 0 days until the umbilical cord is detached by the observation sheet instrument. The results showed that there was a difference of closed and open umbilical cord treatment to the umbilical release length with p.value = 0,000. The average release time of the open care was 98.7 hours, and the closed care was 170.6 hours. There was a difference of 71.9 hours, so it was concluded that there was a significant difference between closed and open umbilical cord care release of the umbilical cord. It is expected to be notified to health workers to know more effective umbilical cord care to avoid the risk infection.